Honokiol ameliorates cisplatin‐induced acute kidney injury via inhibition of mitochondrial fission. (31st March 2022) - Mao, Rui‐wen; He, Shan‐ping; Lan, Jun‐gang; Zhu, Wu‐zheng
Abstract : Background and Purpose: Mitochondrial damage and oxidative stress are crucial contributors to the tubular cell injury and death in acute kidney injury. Novel therapeutic strategies targeting mitochondria protection and halting the progression of acute kidney injury are urgently needed. Honokiol is a small‐molecule polyphenol that exhibits extraordinary cytoprotective effects, such as anti‐inflammatory and anti‐oxidative. Thus, we investigated whether honokiol could ameliorate cisplatin‐induced acute kidney injury via preventing mitochondrial dysfunction. Experimental Approach: Acute kidney injury was induced by cisplatin administration. Biochemical and histological analysis were used to determine kidney injury. The effect of honokiol on mitochondrial function and morphology were determined using immunohistochemistry, transmission electron microscopy, immunoblot and immunofluorescence. To investigate the mechanism by which honokiol alters mitochondrial dynamics, remodelling and resistance to apoptosis, we used transfection experiments, immunoblotting, immunoprecipitation and flow cytometry assay. Key Results: We demonstrated that the prominent mitochondrial fragmentation occurred in experimental models of cisplatin‐induced nephrotoxicity, which was coupled to radical oxygen species (ROS) overproduction, deterioration of mitochondrial function, release of apoptogenic factors and the consequent apoptosis. Honokiol treatment caused notable reno‐protection and attenuated of these cisplatin‐induced changes. Mechanistically, honokiol treatment recovered the expression of SIRT3 and improved AMPK activity in tubular cells exposure to cisplatin, which preserved the Drp1 phosphorylation at Ser637 and blocked its translocation in mitochondria, consequently preventing mitochondrial fragmentation and subsequent cell injury and death. Conclusion and Implications: Our results indicate that honokiol may protect against cisplatin‐induced acute kidney injury by preserving mitochondrial integrity and function by SIRT3/AMPK‐dependent mitochondrial dynamics remodelling.